GABA System as a Target for New Drugs - Kowalczyk, P.; Kulig, K. (Current Medicinal Chemistry, 2014)
4-Aminobutyric acid is an inhibitory neurotransmitter involved in the control of neuronal activity in the mammalian central nervous system. There is considerable direct and indirect evidence that impaired activity of GABAmediated inhibitory synapses may be an important causative factor in experimental and clinical seizure disorders. This review is focused on the recent development of compounds which can influence GABA neurotransmission by affecting the GABA receptors, the plasma-membrane GABA transporters (GATs) and catabolic enzyme GABA-transaminase (GABAT). These compounds have been primarily investigated in relation to epilepsy, but it has also been found that a decrease in GABA neurotransmission appears to be involved in the aetiology of several neurological disorders such as insomnia, spasticity, neuropathic pain, anxiety and other mental disorders.
Keywords: GABA uptake inhibitors